Analysis of service quality on consumer satisfaction data from the central statistics agency of Belitung Regency - Susanti Susanti; Reniati Reniati; Lina Warlina (Global Academy of Multidisciplinary Studies, 2025)
Purpose: This study aims to increase the level of consumer satisfaction with the services provided by the Central Statistics Agency (BPS) of Belitung Regency through the Integrated Statistical Service (PST) by measuring the dimensions of Tangibility, Reliability, Responsiveness, Assurance, and Empathy. Research Methodology: This study employed a quantitative survey method using an administrative approach. Data were collected through questionnaires distributed to 50 respondents, including government employees, private employees, consultants, students, and the general public who directly accessed BPS services. The questionnaire was designed using a Likert scale, and the collected data were analyzed using SPSS and Microsoft Excel. Analytical tools included validity and reliability tests, gap analysis, and Importance-Performance Analysis (IPA). Results: The findings revealed that most consumers were satisfied with BPS services, particularly in terms of reliability, assurance, and empathy. The highest satisfaction was noted in terms of data accuracy and trust in BPS independence, while the lowest scores were in terms of responsiveness and tangibility, especially regarding service speed, clarity of publication information, and availability of facilities. Quadrant analysis highlighted that improving officer responsiveness and the clarity of information should be prioritized. Conclusions: The BPS Belitung Regency has achieved a high level of consumer satisfaction but needs to prioritize improvements in officer performance, data clarity, and service speed to enhance the user experience and maintain trust. Limitation: This research is limited to consumer data that comes directly to BPS offices and does not include online consumer services. Contribution: This study contributes to the literature on public service quality by providing empirical evidence of statistical service performance. It also offers practical recommendations for the BPS to strengthen its service delivery and consumer trust, thereby supporting better data-driven decision-making in the Belitung Regency.